2010
DOI: 10.1007/s00467-010-1451-z
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic proteinuria and the spectrum of diurnal variability of urinary protein excretion in healthy children

Abstract: The aim of this study was to characterize the 24-h and diurnal variability of urinary protein excretion and identify the prevalence of orthostatic proteinuria (OP) in healthy children. Upright, supine, and 24-h total urinary protein (UrTP) and creatinine clearance (CrCl) were measured in 91 healthy children ages 6–19 years. Urinary protein and creatinine excretions were calculated and examined by gender, age, Tanner stage, and body mass index (BMI). Orthostatic proteinuria (OP) was defined as a 24-h UrTP >100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 25 publications
2
44
0
2
Order By: Relevance
“…Such screening is already standard of care in certain other high-risk groups, such as children with type 1 diabetes mellitus 91 and sickle cell disease. 92 Unfortunately, the utility of microalbuminuria as a screening tool may be hampered by a high false-positive rate due to the prevalence of benign proteinurias (such as orthostatic proteinuria 93 or exercise-induced proteinuria 94 ) in the pediatric population. For example, in the NHANES, 8.9% of adolescents had microalbuminuria, although the majority of these had no other risk factors for cardiovascular or renal disease.…”
Section: Figurementioning
confidence: 99%
“…Such screening is already standard of care in certain other high-risk groups, such as children with type 1 diabetes mellitus 91 and sickle cell disease. 92 Unfortunately, the utility of microalbuminuria as a screening tool may be hampered by a high false-positive rate due to the prevalence of benign proteinurias (such as orthostatic proteinuria 93 or exercise-induced proteinuria 94 ) in the pediatric population. For example, in the NHANES, 8.9% of adolescents had microalbuminuria, although the majority of these had no other risk factors for cardiovascular or renal disease.…”
Section: Figurementioning
confidence: 99%
“…It was almost twofold prevalent among 6 -19-year-old than in 20 -39-year-old, increasing continuously starting at 40-year-old [33]. Possible explanation for high prevalence in adolescents might be the influence of orthostatic proteinuria [34]. A positive association was found between albumin excretion rate and pubertal developmental stage [35].…”
Section: Microalbuminuria In Healthy Childrenmentioning
confidence: 88%
“…Microalbuminuria has also been investigated in numerous nephrologic and other diseases, such as microhaematuria [56], sickle cell anemia [30,57], low-birth weight [58], congenital solitary kidneys [59], orthostatic proteinuria [34], metabolic syndrome [28].…”
Section: Microalbuminuria In Different Childhood Diseasesmentioning
confidence: 99%
“…This raises the question of whether these children have orthostatic proteinuria. Orthostatic proteinuria is a benign increase in daytime urine protein excretion without renal pathology and has been described in 4% -20% of healthy children [16,24]. In a previous study by our group, orthostatic proteinuria was associated with a proportional change in creatinine clearance, suggesting that changes in GFR mediate the variation in protein excretion [24].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study on orthostatic proteinuria [24] in this cohort of subjects we found that measured CrCl was higher during the daytime compared to the night and a higher CrCl was associated with an increased risk of orthostatic proteinuria. Our finding of a correlation between total urine creatinine and albumin excretion suggests that the difference in albumin excretion between day and night may be mediated by changes in glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 99%